A polarimetrically oriented X-ray stare at the accreting pulsar EXO 2030+375 - Malacaria Christian; Heyl Jeremy; Doroshenko Victor; Tsygankov Sergey S.; Poutanen Juri; Forsblom Sofia V.; Capitanio Fiamma; Di Marco Alessandro; Du Yujia; Ducci Lorenzo; La Monaca Fabio; Lutovinov Alexander A.; et al. (EDP SCIENCES S A, 2025)
Accreting X-ray pulsars (XRPs) are presumed to be ideal targets for polarization measurements, as their high magnetic field strength is expected to polarize the emission up to a polarization degree of similar to 80%. However, such expectations are being challenged by recent observations of XRPs with the Imaging X-ray Polarimeter Explorer (IXPE). Here, we report on the results of yet another XRP, namely, EXO 2030+375, observed with IXPE and contemporarily monitored with Insight-HXMT and SRG/ART-XC. In line with recent results obtained with IXPE for similar sources, an analysis of the EXO 2030+375 data returns a low polarization degree of 0%-3% in the phase-averaged study and a variation in the range of 2%-7% in the phase-resolved study. Using the rotating vector model, we constrained the geometry of the system and obtained a value of similar to 60 degrees for the magnetic obliquity. When considering the estimated pulsar inclination of similar to 130 degrees, this also indicates that the magnetic axis swings close to the observer's line of sight. Our joint polarimetric, spectral, and timing analyses hint toward a complex accreting geometry, whereby magnetic multipoles with an asymmetric topology and gravitational light bending significantly affect the behavior of the observed source.